2021
DOI: 10.24278/2178-5031.202133101
|View full text |Cite
|
Sign up to set email alerts
|

ANATOMICAL RADIAL VARIATION AND DENSITY IN WOOD OF RUBBER TREE [Hevea brasiliensis (Willd. ex A. Juss.) Muell. Arg.] CLONES

Abstract: The anatomical structure and physical properties of wood change signifcantly among trees of the same species and even among different parts of the same tree. However, studies that characterize radial variation of anatomical characteristics and wood density among clones are scarce, specifcally for the rubber tree [Hevea brasiliensis (Will. ex Adr. De Juss.) Muell]. Thus, the objective of the research was evaluating the anatomical radial variation and density in wood of Hevea brasiliensis clones. For this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The research analysis showed that the greatest fiber length is in the sapwood region, the middle section of the 47-year-old -the value was 2.93 ± 0.13 mm. Comparatively, A. grandiflora has a higher average fiber length than other timbers such as Sorbus terminalis (1.57 mm), reported by Bahmani et al (2020); Terminalia ivorensis (1.20 mm) and Triplochiton scleroxylon (1.30 mm), reported by Awaku (1994); and Hevea brasiliensis (1.18 mm), reported by Amorim et al (2021). Thus, according to IAWA (1989), A. grandiflora is classified as medium-length fiber wood.…”
Section: Discussion 41 Vessels Characteristicsmentioning
confidence: 97%
“…The research analysis showed that the greatest fiber length is in the sapwood region, the middle section of the 47-year-old -the value was 2.93 ± 0.13 mm. Comparatively, A. grandiflora has a higher average fiber length than other timbers such as Sorbus terminalis (1.57 mm), reported by Bahmani et al (2020); Terminalia ivorensis (1.20 mm) and Triplochiton scleroxylon (1.30 mm), reported by Awaku (1994); and Hevea brasiliensis (1.18 mm), reported by Amorim et al (2021). Thus, according to IAWA (1989), A. grandiflora is classified as medium-length fiber wood.…”
Section: Discussion 41 Vessels Characteristicsmentioning
confidence: 97%